Allergic Contact Dermatitis due to Henna Tattoo with Secondary Infection - Fransiska Rismauli Natallya; Marsudi Hutomo (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Recently henna tattoo become popular. Incidence of allergic contact dermatitis due to henna tattoo is increasing. Para-phenylenediamine (PPD) is suspected as a contact sensitizer because it is often added to henna tattoo to make a darker color. Patch test is needed to determine the allergen. Case: A 18 year-old woman with chief complaint itchy redness patches, burning sensation, and blisters containing pus on her lower left arm after she applied henna tattoo on those site 3 days before. It was the second time applying henna and the reaction was appeared. The patient was treated with oral antibiotic for 5 days, oral antihistamine, and wet dressing with NaCL 0.9% for 3 days. Three days after wet dressing, topical corticosteroid was applied, and the lesion resolved. Patch test was performed 10 months later and showed positive reaction to PPD and toluenesulfonamide formaldehyde resin (TSFR). The previous history, patient had allergy to nail polish which TSFR was suspected as a contact sensitizer. Discussion: Allergic contact dermatitis is a hypersensitivity reaction caused by skin contact with an environmental allergen. Prior sensitization is required for allergy to develop. Patch test is the gold standard to determine the allergen. Based on history and physical examination, clinical relevance of patch test showed positive current relevance (possible) for PPD, and past relevance for TSFR. Conclusion: Avoiding the allergens are important in the management of contact dermatitis.Key words: Allergic contact dermatitis, henna tattoo, para-phenylenediamine (PPD), patch test.